Empathy and nonattachment independently predict peer nominations of prosocial behavior of adolescents - Sahdra, Baljinder K.; Ciarrochi, Joseph; Parker, Philip D.; Marshall, Sarah; Heaven, Patrick (Frontiers in Psychology, 2015)
There is a plethora of research showing that empathy promotes prosocial behaviour among young people. We examined a relatively new construct in the mindfulness literature, nonattachment, defined as a flexible way of relating to one’s experiences without clinging to or suppressing them. We tested whether nonattachment could predict prosociality above and beyond empathy. Nonattachment implies high cognitive flexibility and sufficient mental resources to step out of excessive self-cherishing to be there for others in need. Multilevel Poisson models using a sample of 15-year olds (N=1831) showed that empathy and nonattachment independently predicted prosocial behaviours of helpfulness and kindness, as judged by same-sex and opposite-sex peers, except for when boys nominated girls. The effects of nonattachment remained substantial in more conservative models including self-esteem and peer nominations of liking.